Hormetic approaches to the treatment of Parkinson's disease: Perspectives and possibilities. Issue 10 (11th August 2018) - Calabrese, Vittorio; Santoro, Aurelia; Trovato Salinaro, Angela; Modafferi, Sergio; Scuto, Maria; Albouchi, Ferdaous; Monti, Daniela; Giordano, James; Zappia, Mario; Franceschi, Claudio; Calabrese, Edward J
Abstract: Age‐related changes in the brain reflect a dynamic interaction of genetic, epigenetic, phenotypic, and environmental factors that can be temporally restricted or more longitudinally present throughout the lifespan. Fundamental to these mechanisms is the capacity for physiological adaptation through modulation of diverse molecular and biochemical signaling occurring from the intracellular to the network‐systemic level throughout the brain. A number of agents that affect the onset and progression of Parkinson's disease (PD)‐like effects in experimental models exhibit temporal features, and mechanisms of hormetic dose responses. These findings have particular significance since the hormetic dose response describes the amplitude and range of potential therapeutic effects, thereby affecting the design and conduct of studies of interventions against PD (and other neurodegenerative diseases), and may also be important to a broader consideration of hormetic processes in resilient adaptive responses that might afford protection against the onset and/or progression of PD and related disorders.